GREEN SYNTHESIS OF ZINC OXIDE NANOPARTICLES OF TRADESCANTIA SPATHACEA PLANT - PULIPAKA, SHANKARAIAH; SUTTEE, ASHISH; JYOTHI, V.; VANI, R. (International Journal of Applied Pharmaceutics, 2025)
Objective: In this investigation, we worked to determine whenever herbal nanoparticle formulations made from methanolic extracts of Tradescantia spathacea (T. S.) leaves exhibited any acute toxicity. Methods: Male and female mice (n = 5 per group per sex) received dosages of 500, 1000, 2000, 3000, and 5000 mg/kg of T. S. methanolic extract containing zinc oxide (ZnO) nanoparticles. Over the course of 14 d, the mice were studied for changes in behavior and weight, as well as death. Vital organs were also subjected to histological examination. Results: Toxicological symptoms and a 10-30% death rate were caused by doses of 3,000 mg/kg and 5,000 mg/kg, respectively. No side effects were seen at dosages of 1000 mg/kg and 2000 mg/kg. No notable morphological alterations in critical organs were detected during histopathological investigation. The lipid profiles and hypoglycaemic effects were improved by all dosages that were evaluated. Conclusion: According to the results, therapeutic dosages of T. S. ZnO nanoparticles are safe, even at an LD50 greater than 5000 mg/kg. Traditional therapeutic uses of Tradescantia spathacea are now well-supported by the results. Histopathological analyses revealed no significant morphological changes in vital organs.